Implementation of Incentives for Teachers of Al-Qur'an Educational Gardens (TPQ) in the Tuban Regency Government - Khansa Dzakira Kemala Putri; Susi Hardjati (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This research examines the implementation of the incentive policy for Qur’anic Education (TPQ) teachers in Tuban Regency based on Regional Regulation (Peraturan Bupati) No. 3 of 2023. The study is motivated by concerns regarding administrative accuracy, governance consistency, and effectiveness of incentive distribution to non-formal religious educators. The urgency lies in the growing demand for transparent, accountable, and equitable public policy implementation at the local level. This issue is significant because TPQ teachers play a fundamental role in strengthening religious literacy and character development in the community. Therefore, the objective is to analyze the alignment of policy implementation with regulatory standards. The research method used is a qualitative descriptive approach. Data were collected through interviews, document analysis, field observations, and verification of institutional administrative records related to incentive distribution. The analysis was conducted using interactive data analysis techniques, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation generally aligns with Tuban Regent Regulation No. 3 of 2023, but challenges persist, such as a semi-manual administrative system leading to suboptimal efficiency despite digitization of the TPQ teacher database via the Tuban Satu Data platform and delays in accountability reports from some sub-districts. This study recommends comprehensive digitalization, integrating the database with the incentive disbursement system for real-time validation, and regular administrative training for TPQ coordinators by the Tuban Regency Government and BKPRMI to enhance competency. Further research should adopt a participatory approach involving TPQ teachers' perceptions to assess impacts on well-being and teaching motivation.